2019
DOI: 10.1175/jtech-d-18-0220.1
|View full text |Cite
|
Sign up to set email alerts
|

Intermittency in Estuarine Turbulence: A Framework toward Limiting Bias in Microstructure Measurements

Abstract: Intermittent turbulence behavior has a number of implications for field sampling, namely, that if undersampled, it can result in over- or underestimates of turbulent kinetic energy (TKE) dissipation rates. Sampling thresholds and common distributions have previously been defined for oceanic environments, but estuaries remain relatively underrepresented. Utilizing vertical microstructure profilers is a robust way to directly measure TKE dissipation rates; however, microstructure sensors are delicate and conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…In general, VMP and MicroCTD profiles showed a good agreement. While the ε magnitude at specific depths varied between consecutive profiles due to high intermittency of turbulence in a highly stratified coastal environment (e.g., Huguenard et al, 2019), the shape of profiles remained remarkably consistent for each station. Since uprising profiles of MicroCTD provided better nearsurface resolution (within the plume), only those are shown in Figure 9B.…”
Section: Resultsmentioning
confidence: 91%
“…In general, VMP and MicroCTD profiles showed a good agreement. While the ε magnitude at specific depths varied between consecutive profiles due to high intermittency of turbulence in a highly stratified coastal environment (e.g., Huguenard et al, 2019), the shape of profiles remained remarkably consistent for each station. Since uprising profiles of MicroCTD provided better nearsurface resolution (within the plume), only those are shown in Figure 9B.…”
Section: Resultsmentioning
confidence: 91%
“…Nonetheless, this work does indicate that near-surface mixing should be expected downstream of a headland near channel-shoal bathymetry in a macrotidal, low inflow system, typical of many Maine estuaries. For example, former research has identified the tendency for enhanced turbulence to occur near headlands [53,54] and near-surface mixing has been observed in other estuaries with eddies near channel-shoal bathymetry [22,30,55]. Those referenced studies observed near-surface mixing in headland-induced eddies were in the Damariscotta River, Maine, another macrotidal, low-inflow estuary.…”
Section: Eddy-induced Near-surface Mixingmentioning
confidence: 99%
“…The profiler was deployed downward and achieved a terminal velocity of 0.85 m/s after 1.5 m. The instrument was deployed in bursts of 4 casts at each station and averaged in order to limit bias from small scale intermittency. Averaging together four casts has been shown to be sufficient in similar regions with complex morphology [30]. Vertical casts did not reach the bottom, to avoid collision with the sea-bed and damage to the probes.…”
Section: Data Collectionmentioning
confidence: 99%
“…Data were collected in a series of vertical casts, with approximately 5 casts performed every 15 minutes. The 5 casts were averaged and bootstrapped 6,000 times to provide a statistically significant measurement of TKE with depth (Efron & Gong, 1983;Huguenard et al, 2019;Ross et al 2019 and references therein). Turbulence and flocculation properties were also measured at SB_KNO in August 2018 using an MSS-90-S Microstructure Profiler sampling at 1024 Hz.…”
Section: Instrumentationmentioning
confidence: 99%